2019
DOI: 10.3389/fneur.2019.01320
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Iron Accumulation in Deep Gray Matter in Myotonic Dystrophy Type 1 and 2 Using Quantitative Susceptibility Mapping and R2* Relaxometry: A Magnetic Resonance Imaging Study at 3 Tesla

Abstract: Quantitative mapping of the magnetic susceptibility and the effective transverse relaxation rate (R2 * ) are suitable to assess the iron content in distinct brain regions. In this prospective, explorative study the iron accumulation in deep gray matter nuclei (DGM) in myotonic dystrophy type 1 (DM1) and 2 (DM2) and its clinical and neuro-cognitive relevance using susceptibility and R2 * mapping was examined. Twelve classical DM1, four childhood-onset DM1 (DM1 c.o. ), twelve DM2 patients and twenty-nine matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 75 publications
(88 reference statements)
0
10
0
Order By: Relevance
“…Finally, daytime sleepiness or hypersomnolence is a core feature of DM1 brain pathology with the current findings showing strong relationships to low FA. Previous studies have also shown significant relationships between brain pathology and neuroimaging findings with sleep problems, including ventricular enlargement, gray and white matter atrophy, white matter lesions, decreased volume of the pallidum and diencephalon, hypoechogenic raphe, iron accumulation in the caudate nucleus, and decreased neurofibrillary tangles (6,22,26,76,77). Moreover, white matter tract mean diffusivity in the superior longitudinal fasciculus and cingulum has been associated with an increased score on the Epworth Sleepiness Scale (4).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, daytime sleepiness or hypersomnolence is a core feature of DM1 brain pathology with the current findings showing strong relationships to low FA. Previous studies have also shown significant relationships between brain pathology and neuroimaging findings with sleep problems, including ventricular enlargement, gray and white matter atrophy, white matter lesions, decreased volume of the pallidum and diencephalon, hypoechogenic raphe, iron accumulation in the caudate nucleus, and decreased neurofibrillary tangles (6,22,26,76,77). Moreover, white matter tract mean diffusivity in the superior longitudinal fasciculus and cingulum has been associated with an increased score on the Epworth Sleepiness Scale (4).…”
Section: Discussionmentioning
confidence: 98%
“…The majority of studies evaluating depression in DM1 have utilized rating scales such as the Beck Depression Inventory (BDI) (6,9,10,14,16,(22)(23)(24)(25)(26)(27)(28), the Hamilton Rating Scale for Depression (HAM-D) (29)(30)(31)(32)(33)(34) or a variety of other standardized, self-rating scales (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48), and comparison groups were often adults with no major medical illnesses. However, rating scales such as the BDI-II not only assess mood and cognitive symptoms such as sadness, suicidality, and guilt, but also somatic symptoms such as fatigue and sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the neuropsychological disorders, depression in particular, is associated with lesions and atrophy in fronto-temporal and frontal lobes separately [ 20 ]. Our study similarly confirmed that appearance of depression was connected to the lesions of parietal lobe, corpus callosum, simultaneous of frontal lobe and corpus callosum (in group A) and combined lesions of frontal lobe and corpus callosum, fronto-temporal region (in group B), although brain atrophy was associated with depression only in the group of study subjects younger than 40.…”
Section: Discussionmentioning
confidence: 99%
“…At brain MRI, Diffusion Tensor Imaging (DTI) and Voxel Based Morphometry (VBM) techniques show corticospinal tract involvement, as shown by Park et al ( 55 ) who described a significant correlation between gray matter volume loss in the sensorimotor cortex and white matter micro integrity alteration of corticospinal tract (valued with DTI parameters) and motor parameters such as muscle strength (valued by Medical Research Council scale), 6 min walking test (6MWT) and handgrip, suggesting a role of corticospinal alteration in motor performance in DM1. Also, deep gray matter alterations (caudate, pallidum, hippocampus, subthalamic nucleus, thalamus, and substantia nigra) has been described, with significant relationship with motor function, sleepiness and cognitive functions, particularly attention and executive function ( 56 ). CNS involvement also plays a role in sleep disturbance, with prominent REM sleep dysregulation and a narcoleptic-like phenotype in DM1 ( 57 ).…”
Section: Clinical Features Of Cns Involvementmentioning
confidence: 99%
“…Higher Muscular Impairment Rating Scale (MIRS) was associated with lower FA, and patients harboring higher CTG triplets showed a decrease of FA in the fibers, starting in bilateral prefrontal areas, anterior cingulate and temporal cortex insula and putamen ( 61 , 63 ). Ates et al in 2019 with three Tesla MRI studied iron accumulation in deep gray matter nuclei and they found widespread iron accumulation in caudate, pallidum, hippocampus, subthalamic nucleus, thalamus, and substantia nigra; interestingly these alterations were significantly associated with DM1 common symptoms as muscular weakness, daytime sleepiness, and specific cognitive deficit ( 56 ).…”
Section: Clinical Features Of Cns Involvementmentioning
confidence: 99%